Analisis Kepuasaan Pelaksanaan Pendampingan Pengembangan Alat Peraga Edukatif di Pekanbaru, Riau - Iqbal Miftakhul Mujtahid; Mery Berlian; Rian Vebrianto; Musa Thahir (Anotero Lembaga Scientific Pekanbaru, 2020)
This dedication is motivated by the demands of a teacher who must have the ability and skills in making simple APE IPA to increase the achievement of learning goals in schools as required in the curriculum. Therefore, this article aims to gather information about the level of participant satisfaction in participating in assisting the development of educational aids. This community service activity is Participatory Action Research (PAR) carried out using a quantitative descriptive approach method. The data obtained through distributing questionnaires online using google form which were then analyzed descriptively using the help of the SPSS version 23.00 for Windows program. The results of the analysis show that the participants have a good satisfaction level of 71.9% with the satisfactory category.